PEDAGOGICAL PREREQUISITES FOR SUPPORTING STUDENTS WITH LEARNING DIFFICULTIES IN INCLUSIVE EDUCATION - Jurs, Pāvels; Ročāne, Maija; Ekša, Liene (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2023)
Responsibility for the inclusion of students with different learning needs in society should be shared equally by all: teachers, parents, education policy makers, local and national authorities, etc. It is not and should not be the sole responsibility of the educational institution, teachers and professionals of the support team. Inclusive education is an integral component of education policy, while a system of support measures is a key condition for inclusive education. Any student with learning difficulties must receive appropriate support measures in order to be able to learn in mainstream education. It is essential that student`s learning difficulties are identified as early as it is possible, so that individualised and professional support is provided on time. The humanistic pedagogical framework of the chosen teaching and learning strategy is important. Such approach consists of the varied, targeted and professional application of pedagogical approaches and methods appropriate to each student. This is an essential prerequisite for the successful implementation of inclusive education. Using theoretical research methods - analysis of literature and normative acts, as well as empirical research methods - survey, statistical analysis of results and visualisation of data, the aim of the article is to identify existing challenges and develop proposals for successful implementation of inclusive education in comprehensive educational institutions for students with learning difficulties. As a result of the study, the authors developed a number of recommendations for local authorities as school founders, school administrators, teachers and support team professionals in order to help the implementation of inclusive education at schools more effectively. The results of the study confirm the lack of resources for meaningful and effective implementation of inclusive education in educational institutions, as well as reflect the support measures applied by educational institutions for pupils with learning difficulties, identifying influencing factors in the implementation of inclusive education.